Análise cienciométrica da produção científica desenvolvida nos últimos 15 anos sobre a broca-peluda (hyponeuma taltula) em comparação com outras pragas da cana-de-açúcar - Seleghim, David Renato (Universidade Federal de São Carlos, 2021)
Sugarcane culture is of key importance for Brazil. Among the various obstacles found in the production of sugar and alcohol, we can mention the pests that attack the crop. In recent years, with the expansion of planting areas and the prohibition of burning sugarcane fields, new pests of importance to the crop have emerged, among them the hairy borer (Hyponeuma taltula). In this context, the promotion of a scientometric analysis allows to evaluate the scientific production about the hairy borer in comparison with other sugarcane pests, which can help to understand the academic research scenario about this pest of increasing importance, allowing the creation of new perspectives on the species and on the way it has been approached over the last few years in scientific research. Thus, the objective of this work was to carry out a detailed analysis of the scientific research already consolidated on the hairy borer (Hyponeuma taltula) in comparison with other sugarcane pests. For this, a survey of the scientific production developed in the last 15 years (2006-2020) about this pest and other pests of importance for the sugarcane culture was carried out. The search engines that were used to carry out this research were: SciELO, Capes Periodicals, SCOPUS and Google Scholar. The quantity was evaluated in absolute numbers and in terms of percentage of distribution of publications made in a directed way, with the name of the pest in the title of the work, and of publications with the citation of the pest throughout the work. In addition, the distribution of papers on the furred borer by period (every five years), the distribution of papers by topic addressed (biology, behavior, morphology and control) and the distribution of papers by typology (dissertation, journal article, congress abstract, among others). All existing work on the control of H. taltula was also more thoroughly evaluated. From the results obtained, it was possible to observe that the amount of work addressing the hairy borer is still very low compared to works that address other pests of importance to the sugarcane crop, both in a targeted manner (works that objectively address the pest) and in terms of mentions of the pest in other research, compared to other pests of the crop. In addition, it was observed that most of the works about this pest (91.7%) were developed in the last 10 years and that, for the most part, they are magazine articles, with the most discussed theme being the insect's behavior. . In relation to the works found that address the pest control, it can be observed that, for the most part, these are researches in which biological control strategies were tested, with only one work that tested the effectiveness of chemical control. Thus, it was concluded that scientific research on the hairy borer is still incipient and outdated, in comparison with the scientific production directed to other important sugarcane pests, such as D. saccharalis and M. fimbriolata, it is important that researchers and academics pay more attention to this insect.
Scientometric analysis of the scientific production developed in the last 15 years on the hairy borer (hyponeuma taltula) compared to other sugarcane pests
Keywords: Hyponeuma taltula; Análise cienciométrica; Cana-de-açúcar; Pragas; CIENCIAS AGRARIAS::AGRONOMIA